Effects of compaction on the seismic performance of embankments built with gravel. Issue 106 (March 2018) - Modoni, Giuseppe; Albano, Matteo; Salvatore, Erminio; Koseki, Junichi
Abstract: The effects of compaction on the seismic performance of gravelly embankments is investigated transferring the precision of very accurate laboratory tests on the constituent material into the prediction of the large scale response. The stress-strain response observed upon monotonic and cyclic tests is captured by a critical state elastic-plastic model used as a virtual simulator of experiments to determine the influence of the initial state on the soil response. This dependency is introduced in equivalent linear elastic-perfectly plastic models as function of the state variable ψ to study the propagation of shear waves through horizontally layered landfills and embankments. A parametric analysis is performed assigning systematically variable seismic inputs, soil density and geometry to see the role of these factors on the soil response and the sliding resistance of the embankment. The study reveals an exceptionally high resistance of the gravel that enables embankment with steep abutments to resist against severe earthquakes. Highlights: The role of compaction on the seismic response of gravelly embankments is studied. The behaviour of Chiba gravel is observed with monotonic and cyclic tests. A critical state model is used to study the effect of density on the soil response. A parametric analysis is performed on embankments with variable geometry. The study reveals an exceptionally high resistance of the gravel.